THE EFFECTIVENESS OF INSTAGRAM AS A VISUAL REPRESENTATION OF INTERIOR ARCHITECTURE STUDIOS: AUDIENCE PERSPECTIVE - Lilyana Yashila Rahima Surono; Annisa Ullya Rahma; Andreas Rio Adriyanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The rapid growth of digital platforms has transformed how interior design studios communicate their identity and engage with audiences. Instagram, with its visual-centric nature, has become a crucial tool for these studios to represent their works effectively. This study aims to evaluate Instagram's potential in showcasing creativity, building brand identity, and fostering interaction between studios and their audience. Through interviews with 10 respondents from various interior design backgrounds, the findings reveal that Instagram’s features—particularly feeds and reels—enable studios to present their projects dynamically and informatively. Respondents appreciated content that demonstrates ideation processes, project transformations, and technical details, indicating a preference for educational and visually engaging posts. While Instagram excels in creating first impressions and expanding reach, it falls short as a sole platform for deep exploration of studio profiles. Consistent posting, creativity in content, and active audience interaction emerged as critical factors in optimizing Instagram as a representation medium. This research underscores the need for interior design studios to combine Instagram’s capabilities with other platforms to achieve a comprehensive and impactful digital strategy.